2020
DOI: 10.1080/15487733.2020.1829845
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the current landscape of citizen-driven environmental monitoring: a systematic literature review

Abstract: Citizen observatories can be defined as socio-technical constellations designed to make people who are nonprofessional scientists empowered entities. By enabling citizens to monitor their environment via collection and sharing of data, citizen observatories can be viewed as an application or iteration of citizen science. This article contributes to mapping out the current landscape of citizen engagement and participation in environmental monitoring. We draw on a systematic analysis of 57 peer-reviewed papers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Three case studies in Kenya, Myanmar, and Canada were also identified. These results reflect documented trends in the greater use of citizen science in developed countries, especially the United States and Europe, than in developing countries, which often have fewer resources or opportunities to use these approaches (Pocock et al 2019;Rathnayake et al 2020). Researchers have suggested that limited networking, organizational, and collaboration capacities, including the lack of volunteer participation, are the most common reasons why large-scale citizen science programs are rarely found in developing countries (Requier et al 2020).…”
Section: Figure 1 | Monitoring Approach Used In Case Studiesmentioning
confidence: 57%
“…Three case studies in Kenya, Myanmar, and Canada were also identified. These results reflect documented trends in the greater use of citizen science in developed countries, especially the United States and Europe, than in developing countries, which often have fewer resources or opportunities to use these approaches (Pocock et al 2019;Rathnayake et al 2020). Researchers have suggested that limited networking, organizational, and collaboration capacities, including the lack of volunteer participation, are the most common reasons why large-scale citizen science programs are rarely found in developing countries (Requier et al 2020).…”
Section: Figure 1 | Monitoring Approach Used In Case Studiesmentioning
confidence: 57%
“…This stage gives us 234 papers. In Stage 2 (conducting the review stage), involves carrying out the review of relevant articles [7,8,[13][14][15]. Initially, the dataset in the spreadsheet subjected to a round of duplicate removal (n = 20), which produces an overall set of 214 papers.…”
Section: Methodsmentioning
confidence: 99%
“…This step results in the inclusion of papers only related to AI. We include articles like a paper on primary production appraisals as relevant for our review, as such an article not only communicate understanding of the dynamics of this relationship with oceanic food webs, energy process carbon cycle and earth's climate, but also provides an analysis In Stage 2 (conducting the review stage), involves carrying out the review of relevant articles [7,8,[13][14][15]. Initially, the dataset in the spreadsheet subjected to a round of duplicate removal (n = 20), which produces an overall set of 214 papers.…”
Section: Methodsmentioning
confidence: 99%
“…Despite worldwide political support for the development of citizen observatories, including by the European Commission, several reservations have been expressed about the reliability of data obtained via citizen-based observations compared to those obtained by professional researchers, and the lack of quality standards needed for informed decisionmaking and environmental governance. Indeed, there are studies demonstrating limitations in the scalability and reliability of data collected through citizen observatories [19]. Nevertheless, there is also evidence that the citizen-centred approach used by citizen observatories appears to translate into sustained participation by participants, leading to the generation of better-quality data [20].…”
Section: Citizen Observatories: Opportunities To Support the Sdgsmentioning
confidence: 99%